Antimicrobial usage and risk of retreatment for mild to moderate clinical mastitis cases on dairy farms following on-farm bacterial culture and selective therapy. Issue 2 (4th March 2018) - McDougall, S; Niethammer, J; Graham, EM
Abstract : AIMS: To assess antimicrobial usage for treatment of mild to moderate clinical mastitis, and risk of retreatment, following implementation of an on-farm bacterial culture system and selective therapy based on culture results, and to assess compliance with treatment decision tree protocols and the level of agreement between results from on-farm culture and laboratory-based microbiology methods. MATERIALS AND METHODS: Herdowners from seven dairy herds were asked to collect milk samples from cases of mild to moderate clinical mastitis between July 2015 and May 2016. All samples were cultured on-farm using a commercially available selective media and were also submitted for laboratory-based culture. Within sequential pairs of cows with mastitis, half were assigned to be treated without regard to culture results (Blanket group), and half were treated based on the on-farm culture results (Selective group) according to decision tree diagrams provided to the farmers. Culture results, treatments, and retreatments for clinical mastitis were recorded. The sum of the daily doses of antimicrobials used per cow, the number of retreatments and interval to first retreatment were compared between treatment groups. RESULTS: The geometric mean sum of daily doses for quarters assigned to the Selective (1.72 (95% CI=1.55–1.90)) group was lower than for the Blanket (2.38 (95% CI=2.17–2.60)) group (p=0.005). The percentage of cows retreated for clinical mastitis did not differ between the Selective (21.7 (95% CI=10.5–25.9)%) and Blanket (26.1 (95% CI=20.9–31.3)%) groups (p=0.13), and there was no difference between groups in the hazard that cows would be retreated within 60 days of enrolment (hazard ratio=0.82 (95% CI=0.39–1.69); p=0.59). Compliance with the treatment protocols was higher amongst quarters assigned to the Selective (199/233; 85.4%) compared with the Blanket (171/249; 68.7%) group (p<0.001), and varied between farms from 64–94%. The overall agreement between results from on-farm and laboratory culture was 188/331 (56.9%; kappa=0.31; p<0.001), but varied between farms from 44.7–88.2% (p<0.001). CONCLUSIONS: Use of on-farm culture with selective antimicrobial therapy resulted in approximately 25% lower antimicrobial usage, but was not associated with an increase in the proportion of cows retreated for clinical mastitis. CLINICAL RELEVANCE: This study has demonstrated that on-farm culture and selective therapy based on culture results can be implemented on-farm. However, farms varied in their implementation of both the treatment protocols and microbiology procedures. Where such systems are to be used on-farm, specific training and on-going monitoring is required.